Pengaruh Kepuasan Pelanggan, Kualitas Pelayanan Dan Citra Perusahaan Pada Loyalitas Pelanggan PT.Gunung Jati Raya - , Kukuh Suharso, SP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The high level of needs for building materials especially ceramic leads to a very attractive business area in both the industrial and trade sectors. PT. Gunung Jati Raya is a company that is engaged in the distribution of building materials in Central Java. The core business of this company is to distribute building materials, especially ceramics to Central Java and surrounding areas. The company is very concerned about obtaining customers who have high loyalty both to the brand or the company itself as a partner in the attempt. Customer loyalty is an important issue that has become the focus of the company. Loyalty is also the basis for the development of sustainable competitive advantage. The purpose of this study was to determine whether factors of customer satisfaction, service quality factors, and factors of corporate image affect customer loyalty. Sampling method used in this study is the technique of random sampling of probability sampling. Collecting data in this study was done by conducting a survey with direct interviews using questionnaires. The analysis showed that customer satisfaction (X1), quality of service (X2) and corporate image (X3) has positive effects on customer loyalty (Y) of PT. Gunung Jati Raya and the variable Company Image (X3) also acts as a partial mediator variable. Based on the results of regression analysis, customer satisfaction has the strongest influence on customer loyalty with regression coefficient 0.429, followed by quality of service with regression coefficient 0.231 and the company's image with regression coefficient 0.190.